Use Value of Food Plants in the Xi’iuy Indigenous Community of Las Guapas, Rayon, San Luis Potosi, Mexico - Carbajal-Esquivel, Haydeé; Martínez, Javier Fortanelli; García-Pérez, José; Reyes-Agüero, Juan A.; Yáñez-Espinosa, Laura; Bonta, Mark (Ethnobiology Letters, 2012)
Native communities’ erosion of ethnobotanical knowledge of food plants is a global concern. This investigation focuses on a Xi’iuy community in the Sierra Madre Oriental, San Luís Potosí, México. A total of 21 randomly-selected families participated (22% of the total population). The 56 people who were interviewed—an average of 2.7 per family– were separated into four groups (fathers, mothers, single sons, single daughters). To investigate the use value of each plant, a collection of 54 food specimens was shown to the informants. Knowledge of each food species’ uses was compared between genders and age groups. The results included figures that were lower than expected, as well as less knowledge among women than men, particularly among underage daughters. The difference in use value between men and women in this community is explicable by cultural factors: i.e., women’s participation in agriculture and plant collecting is minimal. This, along with men’s seasonal migration for work (men are usually wage laborers half the year in the sugarcane harvest, and the other half they cultivate their own land), plus increasing availability of commercial food in grocery stores, contributes to the steady loss of ethnobotanical knowledge.